2009
DOI: 10.1038/nri2508
|View full text |Cite
|
Sign up to set email alerts
|

B-cell responses to vaccination at the extremes of age

Abstract: Infants and the elderly share a high vulnerability to infections and therefore have specific immunization requirements. Inducing potent and sustained B-cell responses is as challenging in infants as it is in older subjects. Several mechanisms to explain the decreased B-cell responses at the extremes of age apply to both infants and the elderly. These include intrinsic B-cell limitations as well as numerous microenvironmental factors in lymphoid organs and the bone marrow. This Review describes the mechanisms t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
455
1
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 552 publications
(492 citation statements)
references
References 108 publications
16
455
1
3
Order By: Relevance
“…These findings are in contrast to strongly significant changes in concentration of MenC-specific Ab with age at priming immunization with MenC vaccine (25). Siegrist and Aspinall (35) suggest that the large load of environmental Ags in early life causes competition between plasma cells for access to a limited set of survival niches in bone marrow. Therefore, infants and young children have a suboptimal bone marrow plasma-cell pool and poor maintenance of persistent Ab.…”
Section: Menc-specific Memory B Cell Immune Responses Postboostercontrasting
confidence: 53%
See 2 more Smart Citations
“…These findings are in contrast to strongly significant changes in concentration of MenC-specific Ab with age at priming immunization with MenC vaccine (25). Siegrist and Aspinall (35) suggest that the large load of environmental Ags in early life causes competition between plasma cells for access to a limited set of survival niches in bone marrow. Therefore, infants and young children have a suboptimal bone marrow plasma-cell pool and poor maintenance of persistent Ab.…”
Section: Menc-specific Memory B Cell Immune Responses Postboostercontrasting
confidence: 53%
“…It has been postulated that the poor ability of infants to generate persistent Ab to polysaccharide-protein conjugate vaccines is due to a reduced ability to retain and support long-lived plasma cells in the bone marrow (33,34). Additional factors include immaturity of the follicular dendritic cell network and therefore limited germinal center responses (35), limited costimulatory signals (e.g., CD21), decreased and/or delayed affinity maturation, and limited plasma cell supporting factors. Recently, studies in mice have discovered that both the protein and carbohydrate components of the glycoconjugate are processed by the B cell-generating glycan peptides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43 It is particularly reassuring that elderly Japanese subjects 80 years of age are able to mount higher functional antibody responses after PCV7 compared with PPSV23, despite reports of immunosenescence in the elderly. 44 As in other studies with PCV13, 12,19,45 in the current study, PCV13 was shown to have an acceptable safety and reactogenicity profile. Local reactions were mainly mild to moderate in severity and self-limiting, although they were statistically significantly higher among PCV13 recipients than PPSV23 recipients, possibly reflecting the higher immune responses observed after PCV13.…”
Section: Discussionmentioning
confidence: 51%
“…The traditional inactivated influenza vaccine (IIV) -both the old formulation containing three viruses and the more recent preparation with four components -is poorly immunogenic in younger subjects; does not protect a significant number of infants, particularly when mismatched viruses are circulating; and is not licensed for those under 6 months of age [4]. Regarding immunogenicity, younger children are quite similar to the elderly, who, because of the senescence of their immune system, respond poorly to immune stimulation [7]. To overcome these problems and to increase the protective efficacy against influenza in pediatric populations, several attempts have been made to modify the composition or the route of administration of IIV.…”
mentioning
confidence: 99%